'We all have friends like that'. (15th January 2021) - Roper, Lucinda; Sturman, Nancy
Abstract : Medical professionals are in an ideal position to mediate between the benefits and harms of internet-sourced medical information, but there is reluctance by patients to discuss with their doctors information found online. This is the first study undertaken in a rural Australian context, where service limitations mean patients' use of the internet may be especially important. Patients attending general practice clinics (n = 33) were interviewed to discover how they used the internet for health information and how they discussed this with their doctors. Analysis used a constant comparison method, informed by grounded theory and a dramaturgical framework. Most participants used a range of tactics when discussing internet-sourced medical information, including concealment, disguise or upfront apologetic disclosures to avoid undermining the expertise of the doctor. These findings do not confirm predictions made in the past that patients' acquisition of internet health information would alter the power dynamic of the medical consultation. Potentially, proactive, doctor-initiated inquiry about internet medical information may help to normalise patients' internet use, allowing open discussion, so doctors can maximise benefits and reduce harms of internet health information. Further study is required to see if this will be an effective strategy and impact health outcomes.